Soft tissue hydatidosis Seven new cases and literature review - González, Daniel; Ruso, Luis; Torres, Marcos; Vega, Alvaro; Monti, José; di Leoni, Francisco (Cirugía del Uruguay, 2002)
Hydatid disease patho/ogy has a high incidence leve/ in Uruguay. lt is rarely found in subcutaneous ce/fular tissues and striated muse/es, usual/y presenting a tumorous clinica/ structure. This report refers to seven new cases of hydatid echinococcosis [HE] in soft parts. We further present an exhaustive analysis of national and international literature involving the last 20 years. Our series includes patients that were trated in three centers of Florida and Montevideo during the period ranging from 1985 through 2000. We arrived at diagnosis through ultrasound and C.A. T analysis 4 cases] as we/1 as by puncture and evacuation of daughter cysts. Among those patients subject to surgery without prior diagnosis, three suffered intraoperatory rupture of two cysts. The other case was diagnosed by anatomo-patho/ogic procedures. No other cysts located at a visceral site were identified.